Nutrition for Health and Fitness: Sodium in Your Diet: FCS8129/HE696, rev. 1/2018 - Bobroff, Linda B (EDIS, 2018)
The foods you eat and the way you prepare and serve them affect the amount of sodium in your diet. This 5-page fact sheet Written by Linda B. Bobroff, and published by the UF/IFAS Department of Family, Youth and Community Sciences will help you evaluate your sodium intake. edis.ifas.ufl.edu/he696